The Comparison of the Effectiveness of Life Skills and Logo Therapy Training on Communication Skills and Maternal Parenting Stress of Mothers of Children with Intellectual Disability - Sarhangi, Masomeh; Hosseini Nasab, Seyed Davoud; Panahali, Amir (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and purpose: The presence of a mentally retarded child in the family puts all family members, especially the mother, under psychological pressure. The present research was conducted with the aim of comparing the effectiveness of life skills training and meaning therapy on communication skills and parenting stress of mothers of intellectually disabled children. Methods: The research method was a semi-experimental type with a pre-test-post-test design with a control group. The statistical population was all the mothers of children with mental disabilities in the exceptional schools of Urmia city in the academic year of 2019-2019. Using the available sampling method, 60 people were selected as a sample for the research and divided into two experimental groups (40 people) and a control group. (20 people) were appointed. Matson’s questionnaire was used to measure communication skills and Abidin’s questionnaire was used to measure mothers’ parenting stress. Findings: Life skills training was effective in increasing communication skills and reducing parenting stress and its sub-scales (p>0.05). Also, meaning therapy training was effective in increasing communication skills and reducing parenting stress and its sub-scales (p>0.05). Conclusion: two intervention methods of life skills training and meaning therapy can be used to increase communication skills and also reduce parenting stress of mothers of intellectually disabled children in order to optimize their mental health.